1993
DOI: 10.1182/blood.v82.11.3265.3265
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant granulocyte colony-stimulating factor administration to healthy volunteers: induction of immunophenotypically and functionally altered neutrophils via an effect on myeloid progenitor cells

Abstract: We performed a detailed kinetic study on the in vivo effect of a single subcutaneous dose of granulocyte colony-stimulating factor (G-CSF; 300 micrograms) in four healthy individuals on the expression and function of neutrophil Fc gamma receptors (Fc gamma R). G-CSF did not induce Fc gamma RI (CD64) on circulating neutrophils. However, neutrophils newly formed in response to G-CSF were Fc gamma RI positive and were able to perform antibody-dependent cellular cytotoxicity in an Fc gamma RI- dependent way. Fc ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
49
1
2

Year Published

1997
1997
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(57 citation statements)
references
References 44 publications
5
49
1
2
Order By: Relevance
“…The high affinity receptor for monomeric IgG, FcRI, is an early myeloid differentiation marker which is lost at the metamyelocyte stage during normal final maturation of PMN and is therefore not expressed on mature cells. It has been demonstrated that G-CSF acts on committed myeloid progenitor cells rather than on mature cells, so that the precursor cells are strongly induced by G-CSF to express FcRI, ultimately resulting in FcRI positive mature PMN (Kerst et al, 1993a). This study showed that by 96 h, FcRI expression was significantly increased with the 7 .…”
Section: Discussionmentioning
confidence: 67%
“…The high affinity receptor for monomeric IgG, FcRI, is an early myeloid differentiation marker which is lost at the metamyelocyte stage during normal final maturation of PMN and is therefore not expressed on mature cells. It has been demonstrated that G-CSF acts on committed myeloid progenitor cells rather than on mature cells, so that the precursor cells are strongly induced by G-CSF to express FcRI, ultimately resulting in FcRI positive mature PMN (Kerst et al, 1993a). This study showed that by 96 h, FcRI expression was significantly increased with the 7 .…”
Section: Discussionmentioning
confidence: 67%
“…Finally, G-CSF administration was associated with a release into the circulation of LAP-positive immature granulocytes (characterized by low CD16 expression), thus suggesting that G-CSF in vivo can modulate the pathway of granulocytic maturation inducing surface expression of LAP in more immature granulocytes. Low levels of CD16 antigen expression in normal donors after exposure to G-CSF has several possible explanations, including release of immature neutrophils into the circulation, shedding of CD16 molecules as the consequence of induced cell activation and, upon in vitro culture, induction of apoptosis (Terstappen et al, 1990;Kerst et al, 1993;de Haas et al, 1994;Homburg et al, 1995). The release of immature neutrophils from the bone marrow is likely to play a more significant role in vivo for two reasons.…”
Section: Discussionmentioning
confidence: 99%
“…One possibility is that G-CSF affects the functional activity of the granulocytes in the bone marrow, which are then released into the circulation with an increased functional capacity. Another investigation demonstrated that it was probably the neutrophils released from the bone marrow in response to G-CSF, which mediated the increase of CD64-dependent antibody-dependent cellular cytotoxicity (Kerst et al, 1993). Another possible explanation is that it is due to a shift to less mature forms of granulocytes, with activity different to normal mature cells.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo studies on the effect of G-CSF administration on the function of neutrophil granulocytes from healthy individuals have demonstrated enhanced adhesion to nylon wool, phagocytosis, luminol-enhanced chemiluminescence, degranulation, and expression of cell surface antigens (Rapoport et al, 1992;Kerst et al, 1993;de Haas et al, 1994;Xu et al, 1996;Höglund et al, 1997a). The levels of lactoferrin, HNL and elastase in serum/plasma increased during G-CSF administration and signs of mobilization of secretory vesicles had also been shown as further evidence for activation of neutrophil degranulation.…”
mentioning
confidence: 98%
See 1 more Smart Citation